2012
DOI: 10.1016/j.jsps.2011.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, anticonvulsant and neurotoxicity evaluation of some new pyrimidine-5-carbonitrile derivatives

Abstract: A series of 2-[2-(substituted benzylidene) hydrazinyl]-4-(4-methoxyphenyl)-6-oxo-1,6-dihydro-pyrimidine-5-carbonitrile (3-16) were synthesized by refluxing 2-hydrazino-4-(4-methoxy-phenyl)-6-oxo-1,6-dihydro-pyrimidine-5-carbonitrile (2) with different substituted aromatic aldehydes in glacial acetic acid and absolute alcohol mixture (8:2). The compounds were evaluated for their anticonvulsant and neurotoxicity effect. In MES test compounds 2-[2-(4-bromo-benzylidene)-hydrazinyl]-4-(4-methoxyphenyl)-6-oxo-1,6-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…In the present study, N-H stretching modes are observed at 3270, 3210cm -1 for dihydropyrimidine 32 . The νN 5 -H 8 ,νN 7 -H 6 stretching modes are observed at 3369 and 3277cm -1 respectively in FT-IR.…”
Section: Ringsupporting
confidence: 55%
“…In the present study, N-H stretching modes are observed at 3270, 3210cm -1 for dihydropyrimidine 32 . The νN 5 -H 8 ,νN 7 -H 6 stretching modes are observed at 3369 and 3277cm -1 respectively in FT-IR.…”
Section: Ringsupporting
confidence: 55%
“…(Figure 2). [21] In continuation of our work on cyanopyrimidine based hybrids [22,23] as anticancer agents [24] and in a search of new hits, it was envisaged to design and synthesize a series of novel compounds bearing both benzimidazole and cyanopyrimidine with expectations of very encouraging results. Hence, several analogs of benzimidazole pendant cyanopyrimidine derivatives ( Figure 3) were synthesized (7a-j) and evaluated for their in-vitro anticancer activity at National Cancer Institute (NCI) USA, against NCI-60 cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…. Moreover, several researchers have worked on the anticonvulsant potential of pyrimidines and triazines in subsequent years and from their studies, it has been proved that both of these moieties contain antiseizure properties. The distance range such as A, D, and HBD, between the essential pharmacophoric elements of clinically used and designed compounds 4a–t are depicted in Table .…”
Section: Resultsmentioning
confidence: 99%